The Mahfel Performances and the Rituals of El Qaima in Aurès Ne- mammha A Heritage of Entertainment and Rain invocation - touil, Eid (The Algerian Historical Journal, 2026)
This researh paper draws on an important aspect of our cultural heritage, Which is included under the title: The Mahfel Performances and the Rituals of El Qaima in Aurès Ne- mammha ,A Heritage of Entertainment and Rain invocation , and what accompanies it of vocal shaws, equestrain games ,and inherited rituels of optimism about the rain falling, which we aim to research into its ritual origins ,artistic expriessions, symbolic contents . To reath the most important results: the historical roots of the regions heritage, the prominent presence of women, its richness in rituals and manifestations of entertainment , and artistic symbols, especially the lyrical print , and the multiplicity of equestrian games and traditional clothing , and pride in owning a rifle and mastering the arts of firing gunpowder.